Refleksi Terhadap Undangan Allah ke dalam Perjamuan Besar dan Tipikal Respons Manusia (Lukas 14:15-24) - Hadi P. Sahardjo (TE DEUM (Jurnal Teologi dan Pengembangan Pelayanan), 2015)
Through this parable, we can learn about God’s plan about men. His invitation couldn’t be rejected. God’s grace is still abundantly poured on us. But if someone reject it, he/she must give the responsibility to God. The parable symbolizes and represents: the salvation offered to the Jews and their rejection of the Saviour (the first call); indicate the Gentile sinners and harlots who warmly welcomed the Son of God and pressed eagerly into His Kingdom (the second call); and the third call represents the wanderers of outlying Gentile world, the world’s “broken earthenware,” upon whom moral compulsion has to be used. God’s grace always widely opened to everyone, it depend on how we respond on it. We are sure that this parable point to the Kingdom of God and His saving plan upon men and how must we respond it.